IMPLEMENTASI ONLINE SOCIAL NETWORK DEPENDENCY PADA KALANGAN MAHASISWA UNIVERSITAS RIAU PENGGUNA INSTAGRAM - Pangesti, Anggit; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Currently social media or social networking has become commonplace because almost most people have used social media, especially among students who can be said to include digital native generation. The ease with which new communications technology makes its users become dependent. According to Thadani & Cheung (2011) Online Social Network Dependency (OSN Dependency) is defined as an impulse control disorder in which an individual experiences rising tension or arousal before engaging in online social networking sites (Online SNS) and a sense of relief or pleasure after completion of the behavior. The purpose of this study was to determine the level of Instagram social media among Riau University students and what factors were most dominant in influencing the level of social media at the University of Riau.This type of research is quantitative with descriptive approach.Respondents in this study were 166 students of Riau University Social Media Instagram users. How to determine the population of researchers using Unknown Population and samples using accidental sampling technique. Methods of data collection using questionnaires. Data were analyzed using descriptive statistical analysis using SPSS 23.The results of this study show the dependence of this matter seen from the data processing of the seven indicators, the Mood Alteration indicator scores reached 3.39 and on a scale highly dependent, Social Benefit score reached 2.83 and is on the scale dependent, Negative Outcome score 3, 24 on scale, Compulsivity score 3.12 is on a scale dependent, Excessive Time score of 3.26 is on a highly dependent scale, Withdrawal score of 3.27 is on a highly dependent scale, and Interpersonal Control with score of 3.25 is in dependent category. So the conclusion obtained by using the average formula of all indicators is 3.19 which is included in the scaled-scale range. This shows that students of Riau University Depends on social media of Instagram.Keyword: Implementation, Online Social Network, Dependency, Instagram